Chemical composition, in vitro antioxidant, anticholinesterase and antibacterial activities of Linaria scariosa Desf. Issue 10 (19th May 2021) - Ahmed-Chaouch, Meroua; Cheriet, Thamere; Beretta, Giangiacomo; Sarri, Djamel; Bensouici, Chawki; Ouelbani, Rayene; Mancini, Ines; Sekhara, Ines; Seghiri, Ramdane
Abstract: The study was performed on the dichloromethane (DCM), ethyl acetate (EAc) and n -butanol (Bu) fractions (F) obtained from the 80% ethanol extract of Linaria scariosa Desf. aerial parts, collected in the North Eastern region of Algeria. Remarkable total phenolic and flavonoid contents were obtained, mainly for EAcF. These results were in accordance with the antioxidant activity of EAcF against DPPH, ABTS, CUPRAC and reducing power tests. DCMF and BuF exhibited significant cholinesterase activity inhibition of BChE and AChE. Moreover, EAcF displayed only moderate antibacterial activities, especially against S. aureus . The biological results were correlated to the chemical components, deduced by both GC-MS analysis of the fractions and the isolation of hemipholin, pectolinarigenin, antirride, antirrinoside, pectolinarin and linariosise, some of which known to exhibit potent effects on the tested biological activities. The study provides the first biological and chemical investigation on Linaria scariosa Desf (unresolved name). Graphical Abstract: